Structural and microstructure of magnetoresistive ND1-XBAXMNO3 (X=0.2, 0.25, 0.3 and 0.35) - Tan Jong Jee (2023)
The effects of barium doping on the microstructure, structure, electrical, magnetotransport properties and magnetoresistance of Nd,Ba,MnO (x=0.2,0.25,0.3 and 0.35) have been studied. The Nd, Ba, MnO (x=0.2, 0.25, 0.3 and 0.35) samples were prepared via solid state reaction method. All samples showed the orthorhombic structure with Pheum group and no impurities were detected when examined by X-ray diffraction method.